Islamic Republic of Mauritania : Second Review Under the Extended Credit Facility Arrangement, and Request for Modification of Performance Criteria-Press Release; Staff Report; and Statement by the Executive Director for Islamic Republic of Mauritania. (IMF Staff Country Reports; Country Report, 2018)
Program implementation has been satisfactory. Macroeconomic stability has been maintained, external debt has been stabilized, and several reforms have been launched to modernize economic institutions and the policy framework. Growth is expected to accelerate this year to 3 1\2 percent, supported by FDI and public investment. While the outlook is positive owing to sustained growth in non-extractive sectors, the international environment is less favorable than during the first review. Higher oil import prices and lower commodity export prices weigh on the external and fiscal positions; the economy remains dependent on commodity exports; and debt vulnerabilities and poverty remain high. Downside risks related to global economic developments and regional security are elevated. On the upside, development of the offshore gas field could generate large revenues from 2022 despite short-term costs.